Electroseamed steel pipe for linepipe

By optimizing the chemical composition and microstructure of electric-stitched steel pipes, the challenges of achieving high strength, low YR, and excellent low-temperature toughness are addressed, resulting in a line pipe with enhanced performance and durability.

JP2025062178APending Publication Date: 2025-04-14NIPPON STEEL CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023171065
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-02
Publication Date
2025-04-14

AI Technical Summary

Technical Problem

Existing electric-stitched steel pipes for line pipes face challenges in achieving high strength, low yield ratio (YR), and excellent low-temperature toughness, particularly due to inappropriate chemical composition or manufacturing methods that affect the area ratio of island-like martensite (MA) in the electric stitch weld.

Method used

The electric-stitched steel pipe is formulated with a specific chemical composition for the base material and electric stitch weld, including C: 0.060-0.120%, Si: 0.010-0.500%, Mn: 0.5-2.0%, and controlled microstructures to achieve an area ratio of ferrite between 40-80% and island-like martensite between 0.2-10.0% in the base material and weld portions, respectively.

Benefits of technology

This approach results in a line pipe with high strength, low YR, and excellent low-temperature toughness, ensuring the pipe's integrity and performance in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062178000012
    Figure 2025062178000012
  • Figure 2025062178000013
    Figure 2025062178000013
  • Figure 2025062178000001
    Figure 2025062178000001
Patent Text Reader

Abstract

To provide an electroseamed steel pipe for line pipes having high strength, low YR and excellent low temperature toughness, in a base material portion and electroseamed welded portion.SOLUTION: An electroseamed steel pipe for linepipe has a base material portion and an electroseamed welded portion, where the chemical composition of the base material portion has a predetermined chemical composition, a microstructure of the 1 / 2×tB portion of the base material has a ferrite area ratio of 40-80% and an average crystal grain size of 35 μm or less, and the microstructure of the 1 / 4×tS portion of the electroseamed welded portion has a ferrite area ratio of 40-70% and an island martensite area ratio of 0.2-10.0%, with an average crystal grain size of 35 μm or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel pipe, and more particularly to an electric resistance welded steel pipe for line pipe. [Background technology]

[0002] Pipelines are one of the means of transporting crude oil and natural gas, but in recent years, as natural resource extraction areas have become more severe, the environment in which line pipes are laid has also become more severe. One of the effects of this is an increase in the number of submarine pipelines laid on the seabed. There are various methods for laying submarine pipelines. One method, called the reel method, involves making the pipes on land in advance, welding them together, and winding the completed long pipes onto a spool on a barge, which is then unwound while laying the pipe on the seabed at sea. This method allows for efficient laying of submarine line pipes.

[0003] However, when winding and unwinding steel pipes, the steel pipes are subjected to plastic bending. At this time, compressive force is applied to the inside of the bend, which can cause buckling on the inside of the bend and the steel pipe to buckle. If steel pipe buckling occurs, construction work must be stopped, causing enormous damage. It is known that buckling of steel pipes can be prevented by lowering the yield ratio (calculated as yield strength (YS) / tensile strength (TS), expressed as YR) in the longitudinal direction of the steel pipe in the base material and electric resistance welded parts of the steel pipe. Against this background, in addition to steel pipes having sufficient strength to withstand high internal pressure, a low YR in the axial direction of the steel pipe is now required.

[0004] In addition, if brittle fracture occurs in line pipes, oil and natural gas will leak out, leading to enormous damage, so excellent toughness is required. Specifically, it is essential to ensure the properties in Charpy tests for the base material and in CTOD tests for electric resistance welds.

[0005] Therefore, electric resistance welded steel pipes used in the reel method are required to have high strength, low YR and excellent toughness in the base material and electric resistance welded parts.

[0006] For example, Patent Document 1 describes an electric resistance welded steel pipe having excellent toughness in the base material and electric resistance welded parts. In the electric resistance welded steel pipe described in Patent Document 1, the chemical composition of the base metal contains, in mass%, C: 0.04-0.12%, Si: 0.01-0.50%, Mn: 0.5-2.0%, Ti: 0.005-0.030%, Nb: 0.005-0.050%, and N: 0.001-0.008%, with the balance containing Fe and impurities, and when the thickness of the base metal is tB and the thickness of the electric resistance weld is tS, the hardness of the outer surface layer B located at a depth of 1 mm from the outer surface of the base metal minus the hardness of the 1 / 2tB portion is 30HV10 or less, and the hardness of the outer surface layer S located at a depth of 1 mm from the outer surface of the electric resistance weld minus the hardness of the 1 / 2tS portion is 0HV10 or more and 30HV10 or less. Patent Document 1 describes that this provides excellent low temperature toughness.

[0007] Patent Document 2 describes an electric resistance welded steel pipe having excellent toughness in the base metal and electric resistance welded parts. The electric resistance welded steel pipe described in Patent Document 2 contains, by mass%, C: 0.02-0.10%, Si: 0.05-0.30%, Mn: 0.80-2.00%, and Nb: 0.010-0.100%, has a composition in which the carbon equivalent Ceq satisfies 0.25-0.50, and has a structure consisting of a bainitic ferrite phase and / or a bainite phase, and has high strength of a yield strength of 52 ksi or more and high toughness with a ductile-brittle transition temperature vTrs of -45°C or less. The material is a thick hot-rolled steel plate, and the electric resistance welded portion is subjected to induction heating at a minimum temperature of 830°C or more and a maximum temperature of 1150°C or less, and then subjected to electric resistance welded portion heat treatment under conditions of an average cooling rate of 10 to 70°C / s at each position in the thickness direction and a cooling stop temperature of 550°C or less, so that the structure is made of a bainitic ferrite phase and / or a bainite phase, and the ratio of the average grain size at the coarsest grain position to the average grain size at the finest grain position at each position in the thickness direction is 2.0 or less. Patent Document 2 describes that this provides excellent low-temperature toughness. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Publication No. 2020 / 170333 [Patent Document 2] International Publication No. 2015 / 004901 Summary of the Invention [Problem to be solved by the invention]

[0009] The inventors' investigations revealed that if the chemical composition or manufacturing method is inappropriate, the area fraction of island martensite (MA), which is a hard phase, in the electric resistance welded joint may fall outside the appropriate range, which may result in the toughness of the electric resistance welded joint being incompatible with a low YR.

[0010] In Patent Documents 1 and 2, no consideration is given to controlling the above-mentioned MA in the electric resistance welded portion. Therefore, it cannot be said that the low-temperature toughness and low YR of the electric resistance welded portion of the electric resistance welded steel pipes described in Patent Documents 1 and 2 are necessarily sufficient.

[0011] The present invention has been made in view of the above circumstances, and has an object to provide an electric resistance welded steel pipe for line pipe use, which has high strength, low YR and excellent low temperature toughness in the base metal and electric resistance welded parts. [Means for solving the problem]

[0012] The gist of the present invention is as follows. (1) An electric resistance welded steel pipe for line pipe according to one aspect of the present invention has a base material portion and an electric resistance welded portion, The chemical composition of the base material is, in mass%, C: 0.060~0.120%, Si: 0.010 to 0.500%, Mn: 0.5-2.0%, P: 0.030% or less, S: 0.0011~0.0050%, Al: 0.080% or less, Ti: 0.003 to 0.030%, Nb: 0.003 to 0.046%, N: 0.0010~0.0080%, Ca: 0.0003 to 0.0040%, O: 0.005% or less, Cu: 0-0.500%, Ni: 0 to 0.500%, Cr: 0~0.500%, Mo: 0 to 0.500%, V: 0 to 0.100%, W: 0 to 0.500%, REM: 0 to 0.0050%, and The balance is composed of Fe and impurities. Ceq represented by the following formula (i) is 0.16 to 0.53 mass%, M represented by the following formula (ii) is 0.06 to 0.25 mass %, CA represented by the following formula (iii) is 0.25 to 2.00, When the thickness of the base material portion is tB and the thickness of the electric resistance welded portion is tS, In the microstructure of the 1 / 2×tB portion of the base material, The area ratio of ferrite is 40 to 80%, and the average crystal grain size is 35 μm or less. In the microstructure of the 1 / 4×tS part of the electric welded part, The area ratio of ferrite is 40 to 70%, the area ratio of island martensite is 0.2 to 10.0%, and the average crystal grain size is 35 μm or less. Ceq=C+Mn / 6+(Ni+Cu) / 15+(Cr+Mo+V) / 5 …(i) M = C / 3 + 5 × Nb … (ii) CA = Ca / S ... (iii) Here, the content (mass %) of the corresponding element is substituted for each element symbol in the formulas (i), (ii), and (iii), and 0 is substituted when the corresponding element is not contained. (2) The electric resistance welded steel pipe for line pipe described in (1) above is The chemical composition of the base material is, in mass%, Cu: more than 0% and less than 0.500%, Ni: more than 0% and less than 0.500%, Cr: more than 0% and less than 0.500%, Mo: more than 0% and less than 0.500%, V: more than 0% and less than 0.100%, W: More than 0% and 0.500% or less, and REM: more than 0% and 0.0050% or less of one or more selected from the group consisting of may be contained. Effect of the Invention

[0013] According to the above-described aspect of the present invention, it is possible to obtain an electric resistance welded steel pipe for line pipe use having high strength, low YR and excellent low-temperature toughness in the base metal and the electric resistance welded portion. [Brief description of the drawings]

[0014] [Figure 1] FIG. 13 is a diagram showing the relationship between the MA area ratio of an electric resistance welded portion and δc. [Diagram 2] FIG. 1 is a diagram showing the relationship between the MA area ratio of an electric resistance weld and YR. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The present inventors have investigated a method for obtaining an electric resistance welded steel pipe for line pipe use which has high strength, low YR and excellent low temperature toughness in both the base metal and the electric resistance welded part, and have obtained the following findings.

[0016] (I) In the base material, in addition to adjusting the chemical composition of the electric resistance welded steel pipe, it is important to control the microstructure by controlling the hot rolling conditions. In addition, elongated MnS becomes the starting point of brittle fracture and affects the ductile-brittle transition temperature (vTrs). Ca suppresses the formation of elongated MnS. Therefore, controlling the Ca content is important to suppress the formation of elongated MnS. On the other hand, the lower the S content, the less elongated MnS there is. From the above, it is important to control the Ca and S contents in order to suppress the formation of elongated MnS.

[0017] (II) In electric resistance welded steel pipes, when they are as is, the microstructure of the weld becomes a quenched martensite structure and becomes very hard, which significantly deteriorates the toughness. Therefore, in order to improve toughness, electric resistance welded steel pipes are subjected to a heat treatment in which the outer surface side is reheated after electric resistance welding and then water-cooled. Since water cooling is performed on the outer surface, the outer surface side is cooled rapidly, and the hardness of the outer surface side increases, which may deteriorate the toughness of the outer surface side. Therefore, it is important to optimize the water-cooling conditions after reheating and reduce the hardness of the outer surface side. Specifically, it is important to optimize the water-cooling conditions so that ferrite, which is a soft structure, is generated in the microstructure on the outer surface side.

[0018] (III) When carbon is concentrated in untransformed austenite during water cooling after reheating, island martensite (MA) is formed. MA is hard, so if there is a large amount of MA, toughness decreases. On the other hand, MA increases the work hardening ability of the material, so if there is a large amount of MA, tensile strength increases. In order to achieve both low-temperature toughness and low YR of electric resistance welds, it is important to properly control the amount of MA.

[0019] (IV) From the standpoint of chemical composition, the amount of MA in electric resistance welds is affected by the C and Nb contents. C concentrates in untransformed austenite during water cooling after reheating to form MA. Therefore, controlling the C content is important for optimizing the amount of MA. On the other hand, Nb has the effect of halting transformation. The lower the Nb content, the less carbon concentrates in untransformed austenite, suppressing the generation of MA. For these reasons, controlling the C and Nb contents is important for optimizing the amount of MA in electric resistance welds.

[0020] (V) The amount of MA in electric resistance welds is affected by the water cooling stop temperature after reheating. When the water cooling stop temperature is high, the concentration of carbon in the untransformed austenite is promoted, and the MA area ratio increases. On the other hand, when the water cooling stop temperature is low, the concentration of carbon in the untransformed austenite is suppressed, and the MA area ratio decreases.

[0021] The amount of MA in the weld is also affected by the segregation state of the electric resistance weld. When the alloy concentration in the segregation zone is high, carbon concentration in the untransformed austenite is promoted, and the MA area ratio increases. On the other hand, when the alloy concentration in the segregation zone is low, carbon concentration in the untransformed austenite is suppressed, and the MA area ratio decreases. To optimize the segregation state in the electric resistance weld, it is important to optimize the slab heating conditions during the production of hot-rolled steel sheet, which is the raw material for electric resistance welded steel pipes.

[0022] Hereinafter, an electric-welded steel pipe for line pipe according to one embodiment of the present invention, which has been made based on the above findings (electric-welded steel pipe for line pipe according to this embodiment (sometimes simply referred to as electric-welded steel pipe)) will be described. However, the present invention is not limited to the configurations disclosed in the present embodiment, and various modifications are possible without departing from the spirit of the present invention.

[0023] The electric-welded steel pipe for line pipe according to this embodiment has a base material portion and an electric-welded welded portion, and when the base material portion has a thickness tB and the electric-welded welded portion has a thickness tS, in the microstructure of a 1 / 2×tB portion of the base material portion, the area fraction of ferrite is 40 to 80% and the average grain size is 35 μm or less, and in the microstructure of a 1 / 4×tS portion of the electric-welded welded portion, the area fraction of ferrite is 40 to 70%, the area fraction of island martensite (MA) is 0.2 to 10.0%, and the average grain size is 35 μm or less. Hereinafter, each requirement of the electric resistance welded steel pipe for line pipe according to this embodiment will be described in detail.

[0024] 1. Chemical composition of the base material The reasons for limiting each element are as follows. The numerical ranges described below with "~" include the lower and upper limits. Numerical values ​​indicated as "less than" or "greater than" are not included in the numerical range. In the following description, "%" in chemical composition means "mass %" unless otherwise specified.

[0025] The electric resistance welded steel pipe for line pipe according to this embodiment has a steel plate as a base material and a welded portion (electric resistance welded portion) provided at the butt joint of the steel plate and extending in the longitudinal direction of the steel plate. In the electric resistance welded steel pipe according to this embodiment, since no welding material is used when the steel plate is electric resistance welded to form the electric resistance welded steel pipe, the base material and the electric resistance welded portion have substantially the same chemical composition.

[0026] The electric resistance welded steel pipe for line pipe according to this embodiment has a chemical composition in the base metal, in mass%, of C: 0.060-0.120%, Si: 0.010-0.500%, Mn: 0.5-2.0%, P: 0.030% or less, S: 0.0011-0.0050%, Al: 0.080% or less, Ti: 0.003-0.030%, Nb: 0.003-0.046%, N: 0. The composition contains 0.0010 to 0.0080%, Ca: 0.0003 to 0.0040%, O: 0.005% or less, and the balance: Fe and impurities, and has a Ceq represented by formula (i) described below of 0.16 to 0.53 mass%, M represented by formula (ii) described below of 0.06 to 0.25 mass%, and CA represented by formula (iii) described below of 0.25 to 2.00. Each element will be described in detail below.

[0027] C: 0.060~0.120% C is an element that affects the YR of steel. If the C content is too low, the YR cannot be sufficiently reduced in the base metal of the electric resistance welded steel pipe for line pipe. In order to obtain a desired YR in the electric resistance welded steel pipe for line pipe, the C content is set to 0.060% or more. The C content is preferably 0.070% or more. On the other hand, if the C content is too high, the central segregation hardens and the low-temperature toughness of the base material deteriorates. In order to ensure the low-temperature toughness of the base material, the C content is set to 0.120% or less. The C content is preferably 0.100% or less.

[0028] Silicon: 0.010 to 0.500% Silicon is an effective element for deoxidizing steel. If the Si content is too low, the effect of improving the soundness of steel by deoxidization (suppressing the occurrence of defects such as blowholes in steel) cannot be fully obtained. In order to fully obtain this effect and obtain excellent low-temperature toughness in the base material, the Si content is set to 0.010% or more. Preferably, it is 0.100% or more. On the other hand, if the Si content exceeds 0.500%, oxides are formed in the electric resistance welded portion, and the low temperature toughness of the electric resistance welded portion deteriorates. Therefore, the Si content is set to 0.500% or less. The Si content is preferably 0.400% or less.

[0029] Mn: 0.5-2.0% Mn is an element effective in ensuring the strength of the base material. In addition, Mn is an element that contributes to ensuring the toughness of the base material by affecting MnS. In order to obtain a desired strength in the base material, the Mn content is set to 0.5% or more. The Mn content is preferably 0.7% or more. On the other hand, if the Mn content exceeds 2.0%, a hardened phase is generated in the central segregation portion, and the low-temperature toughness of the base material portion is significantly deteriorated. Therefore, the Mn content is set to 2.0% or less. The Mn content is preferably 1.6% or less.

[0030] P:0.030% or less P is an element that affects the low-temperature toughness of steel. If the P content exceeds 0.030%, grain boundary embrittlement is caused in the base material and electric resistance welded parts, and low-temperature toughness is significantly deteriorated. Therefore, the P content is set to 0.030% or less. The lower the P content, the better, and it may be 0%. However, since the substantial lower limit of the P content in mass-produced steel is 0.002%, the P content may be 0.002% or more.

[0031] S: 0.0011~0.0050% S is an element that affects the low-temperature toughness of steel. In order to reduce the S content, it is necessary to add a large amount of flux to the molten steel in the secondary refining of the steelmaking process and then extend the reflux time. Therefore, since reducing the S content leads to increased costs and reduced productivity, the S content is set to 0.0011% or more. The S content is preferably 0.0015% or more. On the other hand, if the S content exceeds 0.0050%, coarse sulfides are generated, and the low-temperature toughness of the base material and electric resistance welded joints deteriorates. Therefore, the S content is set to 0.0050% or less. The S content is preferably set to 0.0040% or less.

[0032] Al: 0.080% or less Al is an effective element as a deoxidizer. However, if the Al content exceeds 0.080%, a large amount of Al oxide is generated, and the low-temperature toughness of the base material and the electric resistance welded part deteriorates. Therefore, the Al content is set to 0.080% or less. The Al content is preferably 0.050% or less. The Al content may be 0%. However, in order to obtain a sufficient deoxidizing effect, the Al content is preferably 0.010% or more.

[0033] Ti: 0.003 to 0.030% Ti is a nitride-forming element and contributes to the refinement of crystal grains by forming nitrides. In order to obtain this effect and ensure the low-temperature toughness of the base material, the Ti content is set to 0.003% or more. The Ti content is preferably 0.010% or more. On the other hand, if the Ti content exceeds 0.030%, the low temperature toughness of the base metal is significantly deteriorated due to the formation of coarse carbonitrides. Therefore, the Ti content is set to 0.030% or less, and preferably 0.025% or less.

[0034] Nb: 0.003 to 0.046% Nb is an element that forms carbides, nitrides and / or carbonitrides, and contributes to improving the strength of steel. Nb is also an element that has the effect of improving the low-temperature toughness of the base material of electric resistance welded steel pipe for line pipe by expanding the non-recrystallization rolling temperature range. Nb also has the effect of stagnating transformation, and is an element that is effective in optimizing MA. To obtain these effects, the Nb content is set to 0.003% or more. The Nb content is preferably 0.010% or more. On the other hand, if the Nb content exceeds 0.046%, a large amount of Nb-based carbonitrides is formed, and the low-temperature toughness of the base metal deteriorates. Therefore, the Nb content is set to 0.046% or less. The Nb content is preferably 0.030% or less.

[0035] N: 0.0010~0.0080% N is an element that forms nitrides, refines the crystal grains of steel, and improves the low-temperature toughness of the base material. In order to obtain this effect and ensure the low-temperature toughness of the base material, the N content is set to 0.0010% or more. On the other hand, if the N content exceeds 0.0080%, a large amount of nitrides is formed, which deteriorates the low-temperature toughness of the base metal, so the N content is set to 0.0080% or less.

[0036] Ca: 0.0003~0.0040% Ca is an element that suppresses the formation of elongated MnS by forming sulfides and contributes to improving the low-temperature toughness of the base metal. Therefore, the Ca content is set to 0.0003% or more. On the other hand, if the Ca content exceeds 0.0040%, a large amount of CaO is formed in the electric resistance welded joint, which deteriorates the low temperature toughness of the electric resistance welded joint. Therefore, the Ca content is set to 0.0040% or less.

[0037] O: 0.005% or less O is an element that affects the low-temperature toughness of steel. If the O content exceeds 0.005%, a large amount of oxide is generated, significantly deteriorating the low-temperature toughness of the base material and electric resistance welded parts. Therefore, the O content is set to 0.005% or less. The lower the O content, the better, and it may be 0%. However, since the substantial lower limit of the O content in mass-produced steel is 0.001%, the O content may be 0.001% or more.

[0038] The electric resistance welded steel pipe for line pipe according to this embodiment basically contains the above elements in its chemical composition with the balance being Fe and impurities. However, in order to improve the strength, low temperature toughness, or other properties, the following optional elements may be further contained within the ranges described below. However, since the inclusion of these elements is not essential, the lower limit of each is 0%.

[0039] In addition, in this embodiment, "impurities" refer to components that are mixed in from raw materials such as ores and scraps, or due to various factors in the manufacturing process, when steel is industrially produced, and which are acceptable within a range that does not adversely affect the characteristics of the electric-welded steel pipe for line pipe according to this embodiment.

[0040] Cu: 0 to 0.500% Cu is an effective element for increasing strength without deteriorating low-temperature toughness. Therefore, Cu may be contained as necessary. To obtain the above effect, the Cu content is preferably more than 0%, and more preferably 0.010% or more. On the other hand, if the Cu content exceeds 0.500%, cracks are likely to occur during heating and electric resistance welding of the steel slab, so even if Cu is contained, the Cu content is set to 0.500% or less.

[0041] Ni: 0 to 0.500% Ni is an element effective in improving low-temperature toughness and strength. Therefore, Ni may be contained as necessary. To obtain the above effects, the Ni content is preferably more than 0%, and more preferably 0.010% or more. On the other hand, if the Ni content exceeds 0.500%, the electric resistance weldability deteriorates, so even if Ni is contained, the Ni content is set to 0.500% or less.

[0042] Cr: 0~0.500% Cr is an element that improves the strength of steel by precipitation strengthening. Therefore, Cr may be contained as necessary. To obtain this effect, the Cr content is preferably more than 0%, and more preferably 0.010% or more. On the other hand, if the Cr content exceeds 0.500%, the hardenability increases, the proportion of bainite in the structure becomes too high, and the low-temperature toughness deteriorates. Therefore, even if Cr is contained, the Cr content is set to 0.500% or less.

[0043] Mo: 0 to 0.500% Mo is an element that improves hardenability and at the same time forms carbonitrides, thereby contributing to improving the strength of steel. Therefore, Mo may be contained as necessary. To obtain the above effects, the Mo content is preferably more than 0%, and more preferably 0.010% or more. On the other hand, if the Mo content exceeds 0.500%, the strength of the steel becomes higher than necessary and the low-temperature toughness deteriorates. Therefore, even if Mo is added, the Mo content is set to 0.500% or less.

[0044] V: 0~0.100% V is an element that forms carbides and / or nitrides and contributes to improving the strength of steel. Therefore, V may be contained as necessary. To obtain the above effects, the V content is preferably more than 0%, and more preferably 0.001% or more. On the other hand, if the V content exceeds 0.100%, the amount of precipitates increases and the low-temperature toughness deteriorates. Therefore, even if V is contained, the V content is set to 0.100% or less.

[0045] W: 0~0.500% W is an element that forms carbides and contributes to improving the strength of steel. Therefore, W may be contained as necessary. To obtain the above effects, the W content is preferably more than 0%, and is preferably 0.100% or more. On the other hand, if the W content exceeds 0.500%, the amount of carbides increases and the low-temperature toughness deteriorates. Therefore, even if W is contained, the W content is set to 0.500% or less.

[0046] REM: 0 to 0.0050% Like Ca, REM is an element that suppresses the formation of elongated MnS by forming sulfides, thereby contributing to improving low-temperature toughness and lamellar tear resistance. Therefore, REM may be contained as necessary. To obtain the above effects, the REM content is preferably more than 0%, and more preferably 0.0010% or more. On the other hand, if the REM content exceeds 0.0050%, the number of REM oxides increases and low-temperature toughness deteriorates, so even if REM is contained, the REM content is set to 0.0050% or less. Here, REM refers to a total of 17 elements consisting of Sc, Y and lanthanides, and the REM content means the total content of these elements.

[0047] As described above, the electric resistance welded steel pipe for line pipe according to this embodiment has a chemical composition in the base material and the electric resistance welded part that contains essential elements, contains optional elements as necessary, and is made up of the balance Fe and impurities.

[0048] In the electric welded steel pipe according to this embodiment, in addition to controlling the content of each element as described above, it is necessary to set Ceq and M, which are determined by the content of each element, within predetermined ranges as described below.

[0049] Ceq:0.16~0.53 mass% Ceq is a value that is an index of hardenability and is expressed by the following formula (i). If Ceq is less than 0.16 mass%, the desired strength cannot be obtained in the base material and the electric resistance welded part. Therefore, Ceq is set to 0.16 mass% or more. Ceq is preferably 0.25 mass% or more, and more preferably 0.30 mass% or more. On the other hand, if Ceq exceeds 0.53 mass%, the low temperature toughness of the base material and electric resistance welded joints deteriorates. Therefore, Ceq is set to 0.53 mass% or less. Ceq is preferably 0.45 mass% or less, and more preferably 0.40 mass% or less.

[0050] Ceq=C+Mn / 6+(Ni+Cu) / 15+(Cr+Mo+V) / 5 …(i) In the above formula (i), each element symbol is substituted with the content (mass%) of the corresponding element, and 0 is substituted when the corresponding element is not contained.

[0051] M:0.06~0.25% by mass M is a value that serves as an index of carbon concentration in untransformed austenite, and is represented by the following formula (ii). If M is less than 0.06 mass%, the desired amount of MA cannot be obtained in the electric resistance welded portion, and YR cannot be reduced. Therefore, M is set to 0.06 mass% or more. M is preferably 0.10 mass% or more, and more preferably 0.12 mass% or more. On the other hand, if M exceeds 0.25 mass%, the MA area ratio increases and the low-temperature toughness of the electric resistance welded joint deteriorates. Therefore, M is set to 0.25 mass% or less. M is preferably set to 0.20 mass% or less.

[0052] M = C / 3 + 5 × Nb … (ii) In the above formula (ii), each element symbol is substituted with the content (mass%) of the corresponding element, and 0 is substituted when the corresponding element is not contained.

[0053] CA: 0.25~2.00 CA is a value that serves as an index of inhibition of the formation of elongated MnS, and is expressed by the following formula (iii). If CA is less than 0.25, a large amount of MnS is formed in the base material, the ductile-brittle transition temperature (vTrs) of the base material increases, and low-temperature toughness deteriorates. Therefore, CA is set to 0.25 or more. CA is preferably 0.30 or more, and more preferably 0.35 or more. On the other hand, if CA exceeds 2.00, Ca sulfides become coarse and the low-temperature toughness of the base metal deteriorates. Therefore, CA is set to 2.00 or less, and preferably 1.80 or less.

[0054] CA = Ca / S ... (iii) However, each element symbol in the above formula (iii) is substituted with the content (mass%) of the corresponding element, and 0 is substituted when the corresponding element is not contained.

[0055] 2. Microstructure As described above, in order to improve the strength and low-temperature toughness of electric resistance welded steel pipe for line pipe, it is important to control the microstructures of the base material and the electric resistance welded part. The microstructures of the base material and the electric resistance welded part are described in detail below. In this embodiment, the thickness of the base material is denoted as tB, and the thickness of the electric resistance weld is denoted as tS. In this embodiment, the electric resistance weld indicates the range from the butt surface of the electric resistance weld to a position 600 μm away in the circumferential direction of the base material (i.e., a range of 1200 μm in total centered on the butt surface).

[0056] <Base material part> [In the microstructure of the 1 / 2×tB part of the base material, the area ratio of ferrite is 40 to 80%] In order to ensure the strength and low-temperature toughness of electric resistance welded steel pipe for line pipe, it is important to control the microstructure of the base material. Specifically, it is necessary that the microstructure of the base material contains 40 to 80% ferrite in terms of area ratio. If the area ratio of ferrite contained in the base material is less than 40%, the low-temperature toughness of the base material will deteriorate. Therefore, the area ratio of ferrite in the base material is set to 40% or more. The area ratio of ferrite is preferably 45% or more, and more preferably 50% or more. On the other hand, if the area ratio of ferrite in the base material exceeds 80%, sufficient strength cannot be obtained in the base material. Therefore, the area ratio of ferrite in the base material is set to 80% or less. The area ratio of ferrite is preferably 75% or less, and more preferably 70% or less.

[0057] In this embodiment, the concept of "ferrite" includes polygonal ferrite and pseudo-polygonal ferrite. The microstructure of the base material may include one or more of pearlite (P), pseudo-pearlite (P'), bainite (B), and retained austenite (γ) as the remaining structure. The concept of "bainite" includes granular bainitic ferrite and bainitic ferrite. The area ratio of these remaining structures may be set to 20 to 60% in relation to the area ratio of ferrite.

[0058] In this embodiment, the "1 / 2×tB portion of the base material" refers to a position of (1 / 2)×tB from the outer surface of the base material in the thickness direction. The reason for limiting the microstructure at the position (1 / 2)×tB from the outer surface of the base material is that the structure at this position affects the low-temperature toughness of the base material. In this embodiment, when simply referring to the surface of an electric resistance welded steel pipe for line pipe, it means the outer surface, not the inner surface.

[0059] Regarding the microstructure of the base material, the proportion (area ratio) of ferrite is measured by the following method. For the base material of an electric resistance welded steel pipe for line pipe, a sample for microstructure observation is taken from a position at 90° in the circumferential direction from the electric resistance welded part so that the cross section parallel to the pipe axis direction (longitudinal direction) and thickness direction becomes the observation surface. The electric resistance welded part can be easily distinguished from the base material part because the bead generated by electric resistance welding is cut. The taken sample for microstructure observation is polished for 30 to 60 minutes using a colloidal silica abrasive. The polished sample is analyzed using EBSP-OIM (trademark) (Electron Back Scatter Diffraction Pattern-Orientation Image Microscopy) to determine the area ratio of ferrite. The field of view is a 200 μm range centered on (1 / 2) × tB from the outer surface in the thickness direction in the thickness direction, and a 500 μm range at any position in the pipe axis direction. The observation magnification is 400 times, and the measurement step is 0.3 μm.

[0060] Specifically, the area ratio of ferrite is determined by the KAM (Kernel Average Misorientation) method implemented in EBSP-OIM (trademark). In the KAM method, any one of the pixels in a regular hexagon in the measurement data is taken as the center pixel. The orientation difference between each pixel is calculated for the first approximation using the six pixels adjacent to this center pixel (total of seven pixels), or the second approximation using the 12 pixels further outward from these six pixels (total of 19 pixels), or the third approximation using the 18 pixels further outward from these 12 pixels (total of 37 pixels). The calculated orientation differences are averaged, and the obtained average value is used as the value of the center pixel. This operation is performed for all pixels.

[0061] In this embodiment, the area ratio of pixels calculated to have an orientation difference of 1° or less to the third approximation relative to the total area of ​​the field of view is defined as the area ratio of ferrite. Those with an orientation difference of more than 1° to the third approximation are defined as structures other than ferrite, such as bainite. Structures other than ferrite are identified with reference to the structure photographs published in "Steel Bainite Photo Collection-1 (published by the Iron and Steel Institute of Japan in June 1992)."

[0062] [In the microstructure of the 1 / 2×tB part of the base material, the average grain size is 35 μm or less] In the electric resistance welded steel pipe for line pipe according to this embodiment, in order to ensure good toughness of the base material, the average crystal grain size in the microstructure of the 1 / 2×tB part of the base material is set to 35 μm or less. If the average crystal grain size exceeds 35 μm, the low temperature toughness of the base material deteriorates. The average crystal grain size is preferably set to 30 μm or less, and more preferably set to 20 μm or less. The lower limit of the average crystal grain size in the microstructure of the 1 / 2×tB portion of the base material is not particularly limited, but may be 1 μm or more, 3 μm or more, or 5 μm or more.

[0063] The average crystal grain size in the microstructure of the 1 / 2×tB portion of the base material is measured by the following method. Using the same sample as that used to measure the ferrite area ratio, the microstructure in the 1 / 2×tB part of the base material is analyzed using EBSP-OIM to determine the average grain size. The field of view is a 200μm range centered on (1 / 2)×tB from the outer surface in the thickness direction, and a 500μm range at any position in the tube axis direction. The observation magnification is 400x, and the measurement step is 0.3μm. From the data obtained by the measurement, the area surrounded by high-angle grain boundaries with an inclination angle of 15° or more is considered to be a grain, and the circle-equivalent diameter of that grain is regarded as the grain size. The average grain size is calculated from the obtained grain size using the AREA FRACTION method. However, the region of 0.25 μm or less in equivalent circle diameter is excluded from the calculation of the average crystal grain size because the region of 0.25 μm or less in equivalent circle diameter cannot be evaluated correctly due to the measurement limit.

[0064] <Electric resistance welded section> [In the microstructure of the 1 / 4×tS part of the electric resistance weld, the area ratio of ferrite is 40-70%] The microstructure of the electric resistance weld can be controlled by reheating the electric resistance weld and then water cooling from the outer surface side. In the electric resistance weld, the hardness on the outer surface side increases, which deteriorates the low temperature toughness. Therefore, in the electric resistance weld steel pipe for line pipe according to this embodiment, the microstructure of the 1 / 4×tS part of the electric resistance weld needs to contain soft ferrite in order to ensure the low temperature toughness of the electric resistance weld.

[0065] Specifically, in the microstructure of the 1 / 4×tS portion of the electric resistance welded portion, the ferrite area ratio must be 40 to 70%. If the ferrite area ratio is less than 40%, the hardness of the outer surface side of the electric resistance welded portion increases, and the low temperature toughness deteriorates. The ferrite area ratio is preferably 45% or more, and more preferably 50% or more. Furthermore, in the microstructure of the 1 / 4×tS portion of the electric resistance welded portion, if the area ratio of ferrite exceeds 70%, the strength of the electric resistance welded portion decreases. The area ratio of ferrite is preferably 65% ​​or less, and more preferably 60% or less.

[0066] [In the microstructure of the 1 / 4×tS part of the electric resistance weld, the area ratio of island martensite (MA) is 0.2 to 10.0%] Island martensite (MA) also has an effect on the low-temperature toughness of electric resistance welds. Since MA increases the initiation point of fracture and hardness, the lower the area fraction of MA, the better the low-temperature toughness of electric resistance welds. Figure 1 shows the relationship between the MA area fraction of electric resistance welds and δc. δc represents the limit opening displacement in a CTOD test at -20°C conducted using the method described below. As shown in Figure 1, as the MA area fraction of electric resistance welds decreases, the limit opening displacement δc in a CTOD test at -20°C increases, and it can be seen that if the MA area fraction is 10.0% or less, δc is 0.15mm or more.

[0067] MA also increases the work hardening capacity, so it also affects the yield ratio (YR). The higher the area ratio of MA, the higher the work hardening capacity and the lower the YR. Figure 2 shows the relationship between the MA area ratio of electric resistance welds and the YR obtained by conducting a tensile test using the method described below. As shown in Figure 2, as the MA area ratio of electric resistance welds increases, the YR of the electric resistance welds decreases, and it can be seen that if the MA area ratio is 0.2% or less, the YR of the electric resistance welds is 90% or less. Unlike the base material, electric resistance welds do not contain hard structures caused by central segregation, so control of the MA area ratio is essential to prevent the YR of electric resistance welds from decreasing.

[0068] Therefore, in the electric resistance welded steel pipe for line pipe according to the present embodiment, in order to achieve both excellent low temperature toughness and low YR of the electric resistance welded part, the area ratio of MA is set to 0.2 to 10.0% in the microstructure of the 1 / 4×tS part of the electric resistance welded part. If the area ratio of MA is less than 0.2%, the work hardening ability is reduced, and the YR of the electric resistance welded part increases. The area ratio of MA is preferably 1.0% or more, more preferably 2.0% or more, and even more preferably 3.0% or more. Furthermore, in the microstructure of the 1 / 4×tS portion of the electric resistance weld, if the area ratio of MA exceeds 10.0%, the low-temperature toughness of the electric resistance weld deteriorates. The area ratio of MA is preferably 8.0% or less, more preferably 7.0% or less, and even more preferably 6.0% or less.

[0069] In this embodiment, the "1 / 4×tS portion of the electric resistance weld" refers to a position that is (1 / 4)×tS from the outer surface of the electric resistance weld in the thickness direction. The reason for limiting the microstructure at the position (1 / 4) × tS from the outer surface of the electric resistance weld in the thickness direction is that the structure at this position affects the low temperature toughness and YR of the electric resistance weld.

[0070] The microstructure of the electric resistance welded portion may contain one or more of pearlite (P), pseudo-pearlite (P'), bainite (B), and retained austenite (γ) as the residual structure. The concept of "bainite" includes granular bainitic ferrite and bainitic ferrite. The area ratio of these residual structures may be 20.0 to 59.8% in relation to the area ratios of ferrite and MA.

[0071] The area ratio of ferrite in the microstructure of the electric resistance welded portion is determined by the following method. A sample for microstructure observation is taken from an electric resistance welded steel pipe for line pipe so that the cross section perpendicular to the pipe axis direction including the electric resistance weld is the observation surface. As described above, in this embodiment, the electric resistance weld indicates the range from the butt surface of the electric resistance weld to a position 600 μm away from the base material in the circumferential direction (i.e., a total range of 1200 μm centered on the butt surface). After the observation surface is mirror-finished by wet polishing, the area ratio of ferrite is measured using EBSD in the same manner as for the base material. The measurement position is a 200 μm range centered on (1 / 4) × tS in the thickness direction from the outer surface in the thickness direction, and a 200 μm range centered on a position 400 μm away from the butt surface of the electric resistance weld in the circumferential direction. The butt surfaces of the electric resistance welded parts can be identified and distinguished from the base material by etching them with nital.

[0072] The area ratio of MA in the microstructure of the electric resistance welded portion is determined by the following method. A sample is taken in the same manner as when the area ratio of ferrite in the electric resistance welded portion was measured. After subjecting the observation surface to REPELLA etching, a microstructure photograph is taken using an optical microscope. In the obtained microstructure photograph, the areas observed as white can be identified as island martensite, and the area ratio of island martensite (MA) is calculated by performing image analysis. The field of view is a 200 μm range centered on (1 / 4) × tS in the thickness direction from the outer surface in the thickness direction, and a 200 μm range centered on a position 400 μm away from the butt surface of the electric resistance welded portion in the circumferential direction. However, areas with a circle equivalent diameter of 1 μm or less are excluded from the area ratio of MA, because MA with a circle equivalent diameter of 1 μm or less does not affect low-temperature toughness and YR. For structures other than ferrite, refer to the structure photographs in "Photo Collection of Bainite in Steel - 1 (published by the Iron and Steel Institute of Japan in June 1992)" to determine the structure.

[0073] [The average grain size in the microstructure of the 1 / 4×tS part of the electric resistance weld is 35 μm or less] In order to ensure good low-temperature toughness in the electric resistance welded portion, it is important to control the area ratio of ferrite and MA as described above, and to refine the microstructure. In the electric resistance welded steel pipe for line pipe according to this embodiment, in order to ensure low-temperature toughness in the electric resistance welded portion, the average crystal grain size is controlled to 35 μm or less in the microstructure in the 1 / 4×tS part of the electric resistance welded portion. If the average crystal grain size exceeds 35 μm, the low-temperature toughness of the electric resistance welded portion deteriorates. The average crystal grain size is preferably 30 μm or less, more preferably 20 μm or less, and even more preferably 15 μm or less. The lower limit of the average crystal grain size is not particularly limited, but may be 1 μm or more, 3 μm or more, or 5 μm or more.

[0074] The average grain size in the electric resistance welded portion is determined in the same manner as in the base material portion. The viewing range is a 200μm range centered on (1 / 4)×tS from the outer surface in the thickness direction, and a 200μm range centered on a position 400μm away from the butt surface of the electric resistance weld in the circumferential direction. Also, the area with a circle equivalent diameter of 0.25μm or less is excluded from the calculation of the average grain size. This is because the area with a circle equivalent diameter of 0.25μm or less does not adversely affect the low temperature toughness of the electric resistance weld.

[0075] 3. Mechanical properties Since the electric resistance welded steel pipe for line pipe according to this embodiment is intended to be used as a line pipe, it is preferable that the yield stress (YS) measured in both the base material and the electric resistance welded part is 360 MPa or more, the tensile strength (TS) is 465 MPa or more, and the yield ratio (YR) is 90% or less. The yield ratio can be calculated by dividing the yield ratio by the tensile strength (YS / TS).

[0076] Furthermore, in the electric resistance welded steel pipe according to this embodiment, the base material preferably has a Charpy impact absorption energy of 150 J or more at -20° C. and a ductile-brittle transition temperature (vTrs) of -40° C. or less. If the base material has a Charpy impact absorption energy of 150 J or more at -20° C. and a ductile-brittle transition temperature (vTrs) of -40° C. or less, it can be determined that the low-temperature toughness is excellent, and sufficient toughness can be ensured even in harsh environments such as cold regions.

[0077] In addition, in the electric resistance welded steel pipe for line pipe according to this embodiment, it is preferable that the critical opening displacement δc in the electric resistance welded portion in a CTOD test at −20° C. is 0.15 mm or more. If the critical opening displacement δc in the CTOD test at −20° C. is 0.15 mm or more in the electric resistance welded portion, it can be determined that the low temperature toughness is excellent.

[0078] The tensile test of the base material is performed using a full-thickness test piece in the longitudinal direction of the electric resistance welded steel pipe for line pipe. The yield strength and tensile strength are measured based on the tensile test results. The tensile test piece of the base material is taken from a portion corresponding to a position 90° circumferentially from the seam of the electric resistance welded steel pipe. The tensile test is performed in accordance with API5CT of the American Petroleum Institute.

[0079] The tensile test of the electric resistance welded part is conducted by taking a round bar test piece in the longitudinal direction of the electric resistance welded steel pipe for line pipe from the 1 / 2×tS part of the welded part of the electric resistance welded steel pipe. The round bar tensile test piece is an ISO6892 proportional test piece with a parallel part diameter of φ12.7mm and a gauge length of 65mm. The yield strength and tensile strength are measured based on the tensile test results. The tensile test is conducted in accordance with ISO6892.

[0080] In the Charpy test to evaluate the low-temperature toughness of the base material, a V-notch Charpy test piece is taken from the center of the wall thickness of the base material of the electric resistance welded steel pipe for line pipe (the part corresponding to the position 90° in the circumferential direction from the butt surface of the electric resistance welded part) so that the longitudinal direction of the test piece is the circumferential direction of the electric resistance welded steel pipe for line pipe. In this case, the depth direction of the V-notch is the longitudinal direction of the steel pipe. The V-notch Charpy test is performed at a test temperature of -20°C, and the impact absorption energy at -20°C is measured. In addition, the V-notch Charpy test is performed by changing the test temperature from 0°C to -80°C in 10°C increments, and a transition curve is drawn with the test temperature on the horizontal axis and the ductile fracture ratio on the vertical axis, and the temperature at which the ductile fracture ratio is 50% is taken as the ductile-brittle transition temperature (vTrs). The Charpy test is performed in accordance with API5CT of the American Petroleum Institute.

[0081] In the CTOD (Crack Tip Opening Displacement) test to evaluate the low temperature toughness of electric resistance welds, electric resistance welded steel pipe for line pipe is cut to a length of 300 mm in the longitudinal direction and 300 mm in the circumferential direction, including the electric resistance weld, to obtain a CTOD test piece including the electric resistance weld. The CTOD test piece is processed so that a fatigue pre-crack is formed on the butt surface of the electric resistance weld, with the depth direction of the fatigue pre-crack running in the longitudinal direction of the steel pipe. The CTOD test piece was subjected to a CTOD test at a test temperature of -20°C in accordance with the provisions of BS7448-1:1991, and the critical opening displacement δc (mm) at -20°C was measured.

[0082] 4. Wall thickness There is no particular limit to the wall thickness of the electric resistance welded steel pipe for line pipe according to this embodiment. However, when used as a line pipe, the wall thickness is preferably 15.0 mm or more, more preferably 17.0 mm or more, from the viewpoint of improving the transport efficiency of the fluid passing through the pipe. On the other hand, the wall thickness of the electric resistance welded steel pipe for line pipe is generally limited to 25.4 mm.

[0083] 5.Outer diameter There is no particular restriction on the outer diameter of the electric resistance welded steel pipe for line pipe according to this embodiment. However, when used as a line pipe, the outer diameter is preferably 304.8 mm or more from the viewpoint of improving the transport efficiency of the fluid passing through the pipe. On the other hand, the outer diameter of the electric resistance welded steel pipe for line pipe is generally limited to 609.6 mm.

[0084] 6. Manufacturing method The electric resistance welded steel pipe for line pipe according to the present embodiment can obtain the above-mentioned effects as long as it has the above-mentioned characteristics, regardless of the manufacturing method. The electric resistance welded steel pipe for line pipe according to the present embodiment can be manufactured, for example, by a manufacturing method including the following steps. (a) A casting process that produces slabs of a given chemical composition (b) Heating process for heating the slab (c) The hot rolling process in which the slab is heated and then hot-rolled to produce hot-rolled steel sheets. (d) The hot-rolled steel sheet after the hot rolling process is cooled and coiled. (e) Electric current welding process in which the hot-rolled steel sheet after the coiling process is uncoiled, rolled into a tubular shape, and electric current welded to produce an electric current welded steel pipe. (f) A heat treatment process for heat treating the electric welded joints of electric welded steel pipes. Preferred conditions for each step will be described below.

[0085] <Casting process> In the casting process, the steel having the above-mentioned chemical composition is melted in a furnace and then cast into a slab. The casting method is not particularly limited, and may be any of ordinary continuous casting, casting by the ingot method, thin slab casting, etc.

[0086] <Heating process> In the heating step, the manufactured slab is heated in a heating furnace. The heating temperature T (° C.) of the slab in the heating furnace is preferably 1100 to 1170° C. The residence time t (min) of the slab in the heating furnace is preferably 100 to 450 min. In this embodiment, the residence time t (min) is the time from when the slab is charged into the heating furnace to when the slab is removed from the heating furnace.

[0087] In the heating step, it is further preferable that F1 defined by the following formula (iv) be 2800 to 3700.

[0088] F1 = (T + 273.15) × log(t) … (iv) In the formula (iv), T is the heating temperature (° C.) in the heating step, and t is the time spent in the furnace (minutes).

[0089] If the heating conditions are not appropriate, the austenite grain size will coarsen during heating, and as a result, the average crystal grain size in the 1 / 2×tB portion of the base material will also coarsen, which may result in a deterioration of the low-temperature toughness of the base material. On the other hand, MA in electric welds is generated along the segregation zone of the electric weld, and when the alloy concentration of the segregation zone is high, the area ratio of MA in the electric weld increases, which may cause the low-temperature toughness of the electric weld to deteriorate. When the alloy concentration of the segregation zone of the electric weld is low, the area ratio of MA in the electric weld decreases, which increases the YR. The segregation zone of the electric weld is affected by the heating conditions during the production of hot-rolled steel sheet, which is the raw material for the steel pipe.

[0090] In this embodiment, the slab is appropriately heated under heating conditions that consider the heating temperature and the time spent in the furnace, thereby suppressing the coarsening of the heated austenite grain size in the slab before hot rolling, and also controlling the segregation zone at the width end of the hot rolled steel sheet, i.e., the electric resistance welded part after electric resistance welding, by diffusing atoms uniformly. Specifically, it is preferable to control the heating temperature and the time spent in the furnace so that F1 represented by the formula (iv) is 2800 to 3700.

[0091] Assuming that the content of each element in the chemical composition of the slab is within the range of this embodiment and that formulas (i), (ii), and (iii) are satisfied, if F1 is less than 2800, even if other manufacturing conditions are satisfied, the MA area ratio of the electric welded joint will increase, and the low-temperature toughness of the electric welded joint may deteriorate. Furthermore, when F1 exceeds 3700, the austenite grain size during heating becomes coarse, and the average crystal grain size of the base material becomes coarse, which may deteriorate the low-temperature toughness of the base material. Furthermore, when F1 exceeds 3700, the MA area ratio of the electric resistance welded part decreases, and the YR of the electric resistance welded part may increase.

[0092] <Hot rolling process> In the hot rolling process, it is preferable that the reduction ratio in the recrystallized region is 2.0 or more and the reduction ratio in the non-recrystallized region is 2.0 or more. In particular, by setting the reduction ratio in the non-recrystallized region to 2.0 or more, it is possible to make the average crystal grain size of the base material 20 μm or less. The boundary between the recrystallized region and the non-recrystallized region is about 900 to 950 °C, depending on the composition of the steel.

[0093] The finish rolling start temperature is preferably 900 to 950° C. in order to ensure low-temperature toughness by rolling in the non-recrystallized region. The hot rolling end temperature (finish rolling end temperature) is preferably at least 770° C. If the hot rolling end temperature is less than 770° C., the rolling will be in a two-phase region, and the toughness of the base material will deteriorate.

[0094] <Winding process> In the coiling process, the steel sheet after the hot rolling process is cooled to a surface temperature in the range of 500 to 650°C so that the average cooling rate at the center of the sheet thickness is in the range of 5 to 80°C / sec, and coiled at that temperature range. The average cooling rate at the center of the sheet thickness can be calculated by heat transfer calculation from the temperature history of the outer surface.

[0095] In order to control the microstructure of the base material of the welded steel pipe for electric line pipe according to this embodiment so that it has a predetermined structure, it is particularly important to control the cooling rate. If the average cooling rate is less than 5°C / sec, ferrite transformation will proceed and the ferrite area ratio may exceed 80%. On the other hand, when the average cooling rate exceeds 80° C. / sec, the cooling rate is too fast, so that ferrite transformation does not occur and the ferrite area ratio may become less than 40%.

[0096] Furthermore, if the cooling stop temperature exceeds 650°C, ferrite transformation occurs after coiling, and the ferrite area ratio may exceed 80%. If the cooling stop temperature (coiling temperature) is less than 500°C, the temperature variation during cooling increases, causing strength variation, and the electric resistance welded steel pipe for line pipe according to this embodiment cannot be stably produced.

[0097] <Electric resistance welding process> Electric resistance welded steel pipe for line pipe is manufactured while uncoiling the coiled hot rolled steel sheet. Specifically, the hot rolled steel sheet is processed into an open pipe by bending using a continuous forming roll. Then, the joint of the open pipe, that is, both end faces in the width direction of the hot rolled steel sheet, are welded by electric resistance welding to manufacture the electric resistance welded steel pipe for line pipe.

[0098] <Heat treatment process> In the heat treatment step, the electric resistance welded portion formed in the electric resistance welding step is heated and then cooled with water from the outer surface side. The heating can be performed by, for example, high-frequency heating.

[0099] Specifically, the electric resistance weld is heated to a temperature range of 870-1070°C, and then cooled by water to a surface temperature of 500°C or less so that the average cooling rate of the 1 / 4×tS part is in the range of 5-30°C / s. The average cooling rate of the 1 / 4×tS part can be calculated by heat transfer calculation from the temperature history of the outer surface. This heat treatment (heating and cooling) makes it possible to control the microstructure of the electric resistance weld (fraction of each structure, average crystal grain size) within the above-mentioned range.

[0100] If the heating temperature is below 870°C, regions that do not transform into austenite during heat treatment will remain, causing the microstructure to coarsen and the average crystal grain size to coarsen, which can result in a deterioration of the low-temperature toughness of the electric resistance weld. Furthermore, if the heating temperature exceeds 1070°C, coarse austenite is generated during heat treatment, which may result in coarsening of the microstructure after cooling and deterioration of the low-temperature toughness of the electric resistance welded joint.

[0101] If the average cooling rate is less than 5°C / s, the ferrite area ratio increases and the strength of the electric resistance welded part may decrease. If the average cooling rate is more than 80°C / s, the ferrite area ratio falls below 40%, and the low-temperature toughness of the electric resistance welded part may decrease.

[0102] If the cooling stop temperature exceeds 500°C, the area ratio of MA in the electric resistance welded joint increases, which may deteriorate the low temperature toughness. EXAMPLES

[0103] The effects of one embodiment of the present invention will be described in more detail below with reference to an example, but the conditions in the example are merely an example of conditions adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to this example of conditions. Various conditions may be adopted in the present invention as long as they do not deviate from the gist of the present invention and achieve the object of the present invention.

[0104] Steel types A1 to A55 having the chemical compositions shown in Tables 1A and 1B (the balance being Fe and impurities) were produced. These steel types A1 to A55 were heated, hot rolled, cooled, and coiled under the conditions shown in Tables 2A and 2B to obtain hot-rolled steel sheets.

[0105] The obtained hot-rolled steel sheet was subjected to bending using a forming roll and electric resistance welding, and the welded portion was heat-treated (heated and water-cooled) under the specified conditions as shown in Tables 2A and 2B to produce an electric resistance welded steel pipe for line pipe. The wall thickness of the produced electric resistance welded steel pipes was in the range of 15.0 to 25.4 mm, and the outside diameter was in the range of 304.8 to 609.6 mm.

[0106] For the obtained electric-resistance welded steel pipe, the area ratio of ferrite and average crystal grain size in the microstructure of the 1 / 2×tB part of the base material, and the area ratio of ferrite, area ratio of island martensite (MA) and average crystal grain size in the microstructure of the 1 / 4×tS part of the electric-resistance welded part were evaluated using the methods described above. The results obtained are shown in Tables 3A and 3B.

[0107] In addition, using the above-mentioned method, tensile tests, Charpy tests at test temperatures ranging from 0°C to -80°C in 10°C increments, and CTOD tests at -20°C were performed to evaluate the strength (yield stress, tensile strength), yield ratio (YR), and low-temperature toughness (impact absorption energy at -20°C, ductile-brittle transition temperature vTrs, and critical opening displacement δc at -20°C). The results obtained are shown in Tables 4A and 4B.

[0108] In both the base material and the electric resistance welded parts, if the yield stress (YS) was 360 MPa or more and the tensile strength (TS) was 465 MPa or more, the electric resistance welded steel pipe for line pipe use was judged to pass the test, since the base material and the electric resistance welded parts had high strength. On the other hand, if the yield stress (YS) was less than 360 MPa or the tensile strength (TS) was less than 465 MPa, the electric resistance welded steel pipe for line pipe use was judged to fail, since the base material and the electric resistance welded parts did not have high strength.

[0109] If the yield ratio (YR=YS / TS) was 90% or less in both the base material and the electric resistance welded part, the electric resistance welded steel pipe for line pipe use was judged to have passed the test as having a low YR in the base material and the electric resistance welded part. On the other hand, when the yield ratio was more than 90%, the electric resistance welded steel pipe for line pipe was judged to be unacceptable since it did not have a low YR in the base metal and electric resistance welded parts.

[0110] In the case where the base metal had a Charpy impact absorption energy of 150 J or more at -20°C and a ductile-brittle transition temperature (vTrs) of -40°C or less, the base metal was deemed to have excellent low-temperature toughness and was judged to have passed the test. On the other hand, in the case where the Charpy impact absorption energy at -20°C was less than 150 J or the ductile-brittle transition temperature (vTrs) exceeded -40°C, the base metal was deemed to have poor low-temperature toughness and was judged to have failed the test.

[0111] In the case where the critical opening displacement δc in the CTOD test at -20°C was 0.15mm or more in the electric resistance welded joint, the electric resistance welded steel pipe for line pipe use was judged to have excellent low-temperature toughness in the electric resistance welded joint and to have passed the test. On the other hand, in the case where the critical opening displacement δc in the CTOD test at -20°C was less than 0.15mm, the electric resistance welded steel pipe for line pipe use was judged to have excellent low-temperature toughness in the electric resistance welded joint and to have failed the test.

[0112] As shown in Tables 1A to 4B, for Test Nos. 1 to 35, the chemical composition and microstructure of the base material were within the range of the present invention, and the microstructure of the electric resistance welded portion was also within the range of the present invention. As a result, it can be seen that electric resistance welded steel pipes for line pipes having high strength, low YR, and excellent low-temperature toughness were obtained. On the other hand, the characteristics of Test Nos. 36 to 66, which are comparative examples, did not satisfy the pass conditions for the reasons described below.

[0113] In test No. 36, the C content exceeded the upper limit of the range of the present invention, and the center segregation hardened, resulting in a deterioration in the low temperature toughness of the base material.

[0114] In Test No. 37, the C content was below the lower limit of the range of the present invention, resulting in an increase in YR in the base material.

[0115] In test No. 38, the Si content exceeded the upper limit of the range of the present invention, and the amount of oxides in the electric resistance weld increased, resulting in a deterioration in the low temperature toughness of the electric resistance weld.

[0116] In test No. 39, the Si content was below the lower limit of the range of the present invention, and deoxidation was insufficient, resulting in deterioration of the base metal toughness.

[0117] In test No. 40, the Mn content exceeded the upper limit of the range of the present invention, and the central segregation of the base material hardened, resulting in deterioration of the low temperature toughness of the base material.

[0118] In Test No. 41, the Mn content was below the lower limit of the range of the present invention, and as a result, sufficient strength was not obtained in the base material and the electric resistance welded joint.

[0119] In test No. 42, the S content exceeded the upper limit of the range of the present invention, and Ca sulfides were coarsened, resulting in a deterioration in the toughness of the base material and the electric resistance welded joint.

[0120] In test No. 43, the Ti content exceeded the upper limit of the range of the present invention, and coarse inclusions were formed, resulting in a deterioration in the low temperature toughness of the base metal.

[0121] In Test No. 44, the Ti content was below the lower limit of the range of the present invention, resulting in coarsening of the average crystal grain size of the base material and deterioration of the low-temperature toughness.

[0122] In test No. 45, the Nb content and M content exceeded the upper limit of the range of the present invention, and coarse inclusions were formed. As a result, the low-temperature toughness of the base metal was deteriorated. In addition, the MA area ratio in the electric resistance welded joint increased, and the low-temperature toughness of the electric resistance welded joint was deteriorated.

[0123] In test No. 46, the Nb content and M were below the lower limit of the range of the present invention. As a result, the average crystal grain size of the base material was coarsened, and the low-temperature toughness of the base material was deteriorated. In addition, sufficient strength was not obtained in the base material. In addition, the MA area ratio in the electric resistance welded part was reduced, and the YR was increased.

[0124] In test No. 47, the N content exceeded the upper limit of the range of the present invention, and coarse inclusions were formed, resulting in a deterioration in the low temperature toughness of the base metal.

[0125] In Test No. 48, the N content was below the lower limit of the range of the present invention, resulting in coarsening of the average crystal grain size of the base material and deterioration of the low-temperature toughness of the base material.

[0126] In test No. 49, the Ca content exceeded the upper limit of the range of the present invention, and a large amount of CaO was formed in the electric resistance welded joint, resulting in a deterioration in the low temperature toughness of the electric resistance welded joint.

[0127] In test No. 50, Ceq exceeded the upper limit of the range of the present invention, and the ferrite fraction decreased, resulting in deterioration of the low temperature toughness of the base material and the electric resistance welded joint.

[0128] In Test No. 51, Ceq was below the lower limit of the range of the present invention, and the ferrite fraction was increased, resulting in insufficient strength being obtained in the base metal and the electric resistance welded joint.

[0129] In Test No. 52, M exceeded the upper limit of the range of the present invention. As a result, the MA area ratio in the electric resistance welded joint increased, and the low temperature toughness of the electric resistance welded joint deteriorated.

[0130] In Test No. 53, M was below the lower limit of the range of the present invention. As a result, the MA area ratio in the electric resistance welded portion decreased, and YR increased.

[0131] In test No. 54, CA exceeded the upper limit of the range of the present invention. As a result, Ca sulfides became coarse and the low-temperature toughness of the base metal was deteriorated.

[0132] In test No. 55, the CA was below the upper limit of the range of the present invention, resulting in a large amount of MnS being generated in the base material, and the low-temperature toughness of the base material was deteriorated.

[0133] In test No. 56, F1 exceeded the upper limit, so the average grain size of the base metal became coarse. As a result, the low-temperature toughness of the base metal deteriorated. In addition, the alloy concentration in the segregation zone of the electric resistance weld became too low, so the MA area ratio in the electric resistance weld decreased and the YR increased.

[0134] In test No. 57, F1 was below the lower limit, so the alloy concentration in the segregation zone of the electric resistance weld was high and the area ratio of MA increased. As a result, the low temperature toughness of the electric resistance weld was deteriorated.

[0135] In test No. 58, the reduction ratio in the non-recrystallized region was below the lower limit, so the average grain size of the base metal became large, and as a result, the low temperature toughness of the base metal deteriorated.

[0136] In test No. 59, the cooling rate after hot rolling was high, and the ferrite area ratio of the base material decreased. As a result, the low temperature toughness of the base material deteriorated.

[0137] In test No. 60, the cooling rate after hot rolling was low, and the ferrite area ratio in the base metal increased. As a result, the base metal did not have sufficient strength.

[0138] In test No. 61, the cooling stop temperature after hot rolling and the coiling temperature were high, and the ferrite area ratio in the base metal increased. As a result, sufficient strength was not obtained in the base metal.

[0139] In test No. 62, the heating temperature of the electric resistance weld was high, and the average grain size of the electric resistance weld became large. As a result, the low temperature toughness of the weld deteriorated.

[0140] In test No. 63, the heating temperature of the electric resistance weld was low, and the average grain size of the electric resistance weld became large. As a result, the low temperature toughness of the electric resistance weld deteriorated.

[0141] In test No. 64, the cooling rate of the electric resistance weld was high, and the ferrite area ratio decreased. As a result, the low temperature toughness of the electric resistance weld deteriorated.

[0142] In test No. 65, the cooling rate of the electric resistance weld was low, and the ferrite area ratio increased. As a result, the electric resistance weld could not obtain sufficient strength.

[0143] In test No. 66, the cooling stop temperature of the weld was high, and the area ratio of MA increased. As a result, the low temperature toughness of the electric resistance weld deteriorated.

[0144] [Table 1A]

[0145] [Table 1B]

[0146] [Table 1C]

[0147] [Table 1D]

[0148] [Table 2A]

[0149] [Table 2B]

[0150] [Table 2C]

[0151] [Table 3A]

[0152] [Table 3B]

[0153] [Table 4A]

[0154] [Table 4B] [Industrial Applicability]

[0155] According to the above-mentioned aspect of the present invention, it is possible to obtain an electric resistance welded steel pipe for line pipe having high strength, low YR and excellent low temperature toughness in the base metal and the electric resistance welded part, and therefore has high industrial applicability.

Claims

1. A base material portion and an electric resistance welded portion are included. The chemical composition of the base material is, in mass%, C: 0.060-0.120%, Si: 0.010-0.500%, Mn: 0.5-2.0%, P: 0.030% or less, S: 0.0011-0.0050%, Al: 0.080% or less, Ti: 0.003 to 0.030%, Nb: 0.003-0.046%, N: 0.0010-0.0080%, Ca: 0.0003-0.0040%, O: 0.005% or less, Cu: 0-0.500%, Ni: 0 to 0.500%, Cr: 0-0.500%, Mo: 0-0.500%, V: 0 to 0.100%, W: 0 to 0.500%, REM: 0 to 0.0050%, and The balance is composed of Fe and impurities. Ceq represented by the following formula (i) is 0.16 to 0.53 mass%, M represented by the following formula (ii) is 0.06 to 0.25 mass %, CA represented by the following formula (iii) is 0.25 to 2.00, When the thickness of the base material portion is tB and the thickness of the electric resistance welded portion is tS, In the microstructure of the 1 / 2 × tB portion of the base material, The area ratio of ferrite is 40 to 80%, and the average crystal grain size is 35 μm or less. In the microstructure of the 1 / 4×tS portion of the electric resistance welded portion, An electric resistance welded steel pipe for line pipe, in which the area ratio of ferrite is 40 to 70%, the area ratio of island martensite is 0.2 to 10.0%, and the average crystal grain size is 35 μm or less. Ceq=C+Mn / 6+(Ni+Cu) / 15+(Cr+Mo+V) / 5...(i) M=C / 3+5×Nb...(ii) CA=Ca / S...(iii) Here, the content (mass%) of the corresponding element is substituted for each element symbol in the formulas (i), (ii), and (iii), and 0 is substituted when the corresponding element is not contained.

2. The chemical composition of the base material is, in mass%, Cu: more than 0% and less than 0.500%, Ni: more than 0% and less than 0.500%, Cr: more than 0% and less than 0.500%, Mo: more than 0% and less than 0.500%, V: more than 0% and less than 0.100%, W: more than 0% and 0.500% or less, and 2. The electric resistance welded steel pipe for line pipe use according to claim 1, further comprising at least one selected from the group consisting of REM: more than 0% and 0.0050% or less.

Citation Information

Patent Citations

  • Thick-walled electric resistance welded steel pipe for line pipe, and method for manufacturing said steel pipe

    WO2015004901A1

  • Electric-resistance-welded steel pipe for line pipe

    WO2020170333A1